Porous poly-ether ether ketone (PEEK) manufactured by a novel powder route using near-spherical salt bead porogens: characterisation and mechanical properties - Siddiq, Abdur R.; Kennedy, Andrew R. (Elsevier, 2015)
Porous PEEK structures with approximately 85% open porosity have been made using PEEK-OPTIMA® powder and a particulate leaching technique using porous, near-spherical, sodium chloride beads. A novel manufacturing approach is presented and compared with a traditional dry mixing method. Irrespective of the method used, the use of near-spherical beads with a fairly narrow size range results in uniform pore structures. However the integration, by tapping, of fine PEEK into a pre-existing network salt beads, followed by compaction and “sintering”, produces porous structures with excellent repeatability and homogeneity of density; more uniform pore and strut sizes; an improved and predictable level of connectivity via the formation of “windows” between the cells; faster salt removal rates and lower levels of residual salt. Although tapped samples show a compressive yield stress N1 MPa and stiffness N30 MPa for samples with 84% porosity, the presence of windows in the cell walls means that tapped structures show lower strengths and lower stiffnesses than equivalent structures made by mixing.